2020
DOI: 10.3389/fped.2020.00454
|View full text |Cite
|
Sign up to set email alerts
|

Immune Monitoring After Allogeneic Hematopoietic Cell Transplantation: Toward Practical Guidelines and Standardization

Abstract: Hematopoietic cell transplantation (HCT) is often a last resort, but potentially curative treatment option for children suffering from hematological malignancies and a variety of non-malignant disorders, such as bone marrow failure, inborn metabolic disease or immune deficiencies. Although efficacy and safety of the HCT procedure has increased significantly over the last decades, the majority of the patients still suffer from severe acute toxicity, viral reactivation, acute or chronic graft-versus-host disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Delayed immune reconstitution with absent RTE generation is associated with increased risks for infection, treatment-related mortality, and chronic GvHD 47 . Markers of immune reconstitution including initiation and maintenance of RTE production are therefore important predictors of overall outcome 48 . The assessment of thymic function in pediatrics is not standardized and previous reports mainly rely on reaching specific absolute numbers of CD45RA+expressing CD4 T cells independent of the age of the child 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed immune reconstitution with absent RTE generation is associated with increased risks for infection, treatment-related mortality, and chronic GvHD 47 . Markers of immune reconstitution including initiation and maintenance of RTE production are therefore important predictors of overall outcome 48 . The assessment of thymic function in pediatrics is not standardized and previous reports mainly rely on reaching specific absolute numbers of CD45RA+expressing CD4 T cells independent of the age of the child 49 .…”
Section: Discussionmentioning
confidence: 99%
“…In summary, there is a unique opportunity to standardize conditioning protocols for NMD 54 and MD 55 and to use longitudinal RTE-reconstitution assessment tools -as suggested herein pediatric allo-HSCT to further analyze the impact of underlying disease, toxicity of conditioning, serotherapy and GvHD on long-term thymic function after allo-HSCT which is of great relevance to detect and prevent precocious immunosenescence, malignancy and autoimmune disease 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Children considered for CD19-targeted immunotherapy are to a large extent in post-HSCT and possibly in their immune-reconstitution phase. There are several parameters that will impact on the kinetics of T-cell recovery after HSCT, such as the conditioning regimens, donor type and age, graft manipulation, type of graft-vs-host disease (GvHD), as well as treatment and prophylaxis [reviewed in ( 73 )]. In children followed for T cell recovery after HSCT for hematological malignancies, studies suggest that recent thymic emigrants and TRECs recover within 6–12 months post-HSCT ( 11 , 74 , 75 ).…”
Section: T Cell Immunity At Cancer Diagnosis and Post-therapy In Chilmentioning
confidence: 99%
“…Previous studies have shown that immune reconstitution is a dynamic process that involves different subpopulations of immune cells, each with its own reconstitution pattern and kinetics. Moreover, immune reconstitution varies greatly among individuals and is influenced by multiple factors related to the donor, the recipient, and the transplantation procedure [4][5][6][7][8]. Most of the previous studies have focused on the reconstitution of T cells and natural killer (NK) cells, which play key roles in cellular immunity [9][10][11].…”
Section: Introductionmentioning
confidence: 99%